Влияние ионной силы на ферментативную активность тромбина - Пехник, И.В.; Селищева, М.Ю.; Серейская, А.А. (Биополимеры и клетка, 1990)
Исследовано влияние ионной силы среды на активность тромбина (TP) при действии его на фибриноген (ФГ) и низкомолекулярный субстрат. Сделан вывод о том, что условия низкой ионной силы (1 = 0,05—0,07) благоприятны для специфического взаимодействия TP с ФГ, не затрагивающего активного центра фермента. Досліджено вплив іонної сили середовища на активність тромбіну (TP) за дії його на фібриноген (ФГ) і низькомолекулярний субстрат. Зроблено висновок про те, що умови низької іонної сили (І = 0,05–0,07) є сприятливими для специфічної взаємодії TP з ФГ, яка не зачіпає активного центра ферменту. The dependence of human a-thrombin and its non-clotting y-form activity have been studied for their dependence on ionic strength of the medium relative to the action on fibrinogen and low-molecular tripeptide substrate. The previously found Rotoli effect of stimulation of fibrinogen clotting by thrombin with ionic strength much lower as against its physiological level (up to I 0.05) is confirmed. Acceleration of both fibrinogen proteolysis by thrombin and the non-enzymic stage of the process, namely, polymerization of fibrin monomer was shown to underlie this phenomenon. During the low-molecular substrate hydrolysis by both forms of thrombin and trypsin no low ionic strength stimulation was observed. The data obtained permit concluding that due to the ionic strength decrease the conditions favourable for thrombin specific interaction (outside its active centre) with fibrinogen by means of long distrance electrostatic coupling between them are created.